Taxation and Returns: A Rejoinder - Fraser, L. M. (Review of Economic Studies, 1934)
Journal Article A Rejoinder Get access L. M. Fraser L. M. Fraser Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 2, February 1934, Pages 141–143, https://doi.org/10.2307/2967620 Published: 01 February 1934